Pengaruh Kepemimpinan Transformasional dan Kepuasan Kerja Terhadap Komitmen Organisasional (Studi Pada Aerowisata Sanur Beach Hotel) - Pradifta, Ngurah Bagus Hendra; Sudibia, Gede Adnyana (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
This study aims to examine and analyze the effect of transformational leadership and job satisfaction on organizational commitment. Data was collected through questionnaires to 70 employees spread hotel. This study used a sample saturated with spread questionnaires to 70 employees as a respondent. The data analysis technique used is the analysis of the path (path analysis). The results showed that transformational leadership is directly significant positive effect on job satisfaction. Transformational leadership has a significant positive direct effect on organizational commitment. Neither job satisfaction has a significant positive direct effect on organizational commitment.
Keywords: Transformational leadership, Job Satisfaction, Organizational Commitment.